DEVELOPING FOR LEARNING FOR NON-FORMAL EDUCATION BY USING PA’PASENG OGI IN THE TASAWUF - Sudirman Sudirman; Budiman Budiman (Universitas Muhammadiyah Enrekang, 2019)
The research study investigated Indonesian learners’ approach of two reading approaches Pappaseng Ogi their perceived contact on effectiveness, and the association between reading approach and effectiveness on their English for Bugis’s Falsafah reading comprehension. Fifty-Three English for Bugis’s Falsafah-major freshmen from participated in these lessons. There is a parallelism of thought between Sufism and modern physics, where Sufism is based on direct understanding into the realm of reality and modern physics based on observations of natural phenomena and scientific experiments that are interpreted and communicated through words that will become too abstract when close together with reality which causes awareness of facts.Sufism has very many values in modern physics, but this may not be realized by the Islamic Ummah. Yet in Sufism which takes verses from the Qur'an a lot of things that are actually in modern physics quantized in the form of formulas, which we can take as the rationality of the highest existence of the Creator (Allah Subhaanahu Wa Ta'ala) so that modern physics can be used as a dissection of the verses of the Qur'an in showing the nature of spirituality.